Adverse childhood experiences: impacts on adult mental health and social withdrawal - Wakuta, Manabu; Nishimura, Tomoko; Osuka, Yuko; Tsukui, Nobuaki; Takahashi, Michio; Adachi, Masaki; Suwa, Toshiaki; Katayama, Taiichi (Frontiers in Public Health, 2023)
Background Adverse childhood experiences (ACEs) have been found to negatively impact adult mental health outcomes. Numerous studies have highlighted on ACEs in family and community settings. However, few have examined the impact of ACEs in school settings, despite the potential influence on social participation. Hikikomori, characterized by severe social withdrawal, was first studied in Japan and has gained recognition in recent years. The present study aims to present the concept of ACEs specific to schools and investigate the impact of both school ACEs and traditional ACEs on adult mental health and Hikikomori. Methods A total of 4,000 Japanese adults, aged 20–34, were recruited through an Internet survey form. All data were obtained in October 2021. Participants answered questions regarding their ACEs in the family (10 items), school ACEs (five teacher-related items and two bullying-related items), depressive/anxiety symptoms, and Hikikomori (remaining at home for more than 6 months). Results A significant association with depressive/anxiety symptoms was shown in both ACEs and school ACEs. An increase of one point in the ACE scores was associated with a 24% increase in the risk of depressive/anxiety symptoms. School ACE scores also demonstrated a significant association with depressive/anxiety symptoms, with an increase of one point associated with a 44% increase in the risk of these symptoms. As for Hikikomori, a significant association was shown in the school ACEs only: a 29% increased risk of Hikikomori for every one-point increase in school ACE scores. Both school ACE scores for teacher-related and bullying-related factors revealed a significant association with Hikikomori; the rates of increased risk were 23 and 37%, respectively. Conclusion These results suggest that school ACEs, rather than ACEs in the family, are associated with the risk of Hikikomori. School ACEs are important for social adaptation, and reducing traumatic experiences in school settings may have the potential to prevent problems in later life, specifically in terms of social participation.